Application of modal-phase domain relations to estimate transmission line parameters - Pineda, Julia T. R. [UNESP]; Kurokawa, Sergio [UNESP] (Inst Engineering Technology-iet, 2019)
The accuracy of transmission line parameters (TLPs) allows the proper response to faults or load variations and the monitoring of common fault indicators, such as the conductor's temperature and sag. TLP estimation methodologies based on modal decomposition theory are restricted to specific tower configurations in which the transmission line transformation matrix is known. This paper proposes a non-linear system of equations to estimate the parameters of a generic three-phase transmission line while using modal-phase relations for an unknown transformation matrix and known voltages and current phasors at the terminals of the line. The Newton-Raphson (NR) method is implemented to solve this proposed system of equations and accurately estimate the TLPs. The relative error of the estimated parameters shows the methods' accuracy and the influence of the line representation as lumped elements. The results demonstrate the robustness and efficiency of the proposed method for transmission lines of different lengths.